Towards rabies elimination in the Asia-Pacific region: From theory to practice. (March 2020) - Rupprecht, Charles E.; Abela-Ridder, Bernadette; Abila, Ronello; Amparo, Anna Charinna; Banyard, Ashley; Blanton, Jesse; Chanachai, Karoon; Dallmeier, Kai; de Balogh, Katinka; Del Rio Vilas, Victor; Ertl, Hildegund; Freuling, Conrad; et al.
Abstract: Rabies is a major neglected zoonotic disease and causes a substantial burden in the Asian region. Currently, Pacific Oceania is free of rabies but enzootic areas throughout southeast Asia represent a major risk of disease introduction to this region. On September 25–26, 2019, researchers, government officials and related stakeholders met at an IABS conference in Bangkok, Thailand to engage on the topic of human rabies mediated by dogs. The objective of the meeting was focused upon snowballing efforts towards achieving substantial progress in rabies prevention, control and elimination within Asia by 2030, and thereby to safeguard the Pacific region. Individual sessions focused upon domestic animal, wildlife and human vaccination; the production and evaluation of quality, safety and efficacy of existing rabies biologics; and the future development of new products. Participants reviewed the progress to date in eliminating canine rabies by mass vaccination, described supportive methods to parenteral administration by oral vaccine application, considered updated global and local approaches at human prophylaxis and discussed the considerable challenges ahead. Such opportunities provide continuous engagement on disease management among professionals at a trans-disciplinary level and promote new applied research collaborations in a modern One Health context. Highlights: Rabies is an acute, progressive incurable viral encephalitis of mammals, including domestic animals, wildlife and humans. A global plan to eliminate canine-mediated human rabies has been developed as a 2030 goal. A 2019 IABS conference in Bangkok, Thailand brought together rabies researchers, regulators and subject matter experts. Participants discussed regional rabies epidemiology, prevention options, current challenges & new opportunities. The conference concluded that canine rabies elimination in Asia will protect the Pacific region from rabies introduction.